Bridging the gap in mental health literacy: co-adapting and feasibility testing a digital intervention to improve mental health literacy amongst young people aged 12–14 in the UK - Vicary, Emily; Brierley, Helen; Wilkinson, Jack; Adesina, Melody; Bee, Penny; Lovell, Karina; Uzun, Naz; Bee, Emily; Brooks, Helen (Frontiers in Psychiatry, 2025)
BackgroundDigital interventions have shown promise in enhancing mental health literacy among young people (YP). Initially developed in Indonesia, the Improving Mental Health Literacy Among Young People in Indonesia (IMPeTUs) intervention is a co-produced digital application designed to improve mental health literacy and self-management of anxiety and depression in YP. This study aimed to co-adapt the IMPeTUs intervention with YP in the UK and evaluate the feasibility of conducting a future definitive trial in education and community settings.MethodsThe study consisted of two phases. Phase 1 involved co-adapting the intervention through consultations with 49 stakeholders, including YP, parents, and professionals, using principles of experience-based co-design. ‘Co-adapting’ and ‘co-creating’ refer to collaborative modification and development of intervention content with stakeholders. Then, Phase 2 was a multi-site, cluster-randomized feasibility trial with a nested mixed-methods process evaluation conducted at two community sites (N = 19, 12 completing 4-week post-intervention data and 11 completing 3-month follow-up). The ‘nested process evaluation’ assessed acceptability and engagement alongside the trial.ResultsIn Phase 1, the digital intervention was co-adapted with stakeholders to include expanded customization options, UK-specific content, and a new chapter on resilience, healthy relationships and self-care to improve engagement and support mental health literacy. Phase 2 showed the application was well-received, with YP appreciating its relatable storylines and problem-solving focus. Recruitment challenges and lengthy questionnaires highlighted the need for improved partnerships with schools and streamlined data collection. Despite these issues, the usability of the core design was validated, and recommendations to enhance engagement, such as reducing text and adding interactive features, were identified. Exploratory analyses suggested potential improvements in mental health literacy and well-being, although these results require confirmation in a well-powered trial.ConclusionThis study highlights the feasibility of co-adapting and implementing digital interventions to improve mental health literacy among YP within community settings. Future work should focus on refining recruitment strategies for school environments, streamlining data collection, and enhancing engagement features to ensure scalability and effectiveness in large-scale evaluations. These findings lay the foundation for further development and rigorous digital mental health literacy intervention assessment.Clinical trial registrationhttps://doi.org/10.1186/ISRCTN16116467, identifier ISRCTN16116467.